The positive effects of wet cupping therapy on thiol disulfide balance - Savas, Hasan Basri; Sarikan, Ismail (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the oxidant and antioxidant effects of wet cupping therapy on thiol disulfide balance. Method: The cross-sectional study was conducted at Alanya Training and Research Hospital, Turkey, from March 15 to September 15, 2021, and comprised volunteers who received two sessions of wet cupping therapy with an interval of four weeks. Blood samples were taken before the session and then again after the session. Total thiol, native thiol and disulfide were measured in the blood samples using the colorimetric method. Data was analyzed using SPSS 26. Results: Of the 50 subjects with mean age 47.10±15.16 years, 25(50%) were males and 25(50%) were females. There was a statistically significant difference between baseline and post-intervention levels of total thiol, disulfide, reduced thiol ratio, oxidized thiol and thiol oxidation reduction (p<0.001). Conclusion: Wet cupping therapy could remove oxidants, reduce oxidative stress and produce antioxidant effects. Key Words: Cupping therapy, Antioxidant activity, Oxidative stress, Traditional medicine, Thiols, Disulfide.